The regulation of transendothelial migration: new knowledge and new questions. (18th May 2015) - Muller, William A.
Abstract: Leucocyte transendothelial migration (TEM) involves a co-operative series of interactions between surface molecules on the leucocyte and cognate counter-ligands on the endothelial cell. These interactions set up a cascade of signalling events inside the endothelial cell that both allow for the junctions to loosen and for membrane to be recruited from the lateral border recycling compartment (LBRC). The LBRC is thought to provide an increased surface area and unligated receptors to the leucocyte to continue the process. The relative importance of the individual adhesion/signalling molecules that promote transmigration may vary depending on the type of leucocyte, the vascular bed, the inflammatory stimulus, and the stage of the inflammatory response. However, the molecular interactions between leucocyte and endothelial cell activate signalling pathways that disengage the adherens and tight junctions and recruit the LBRC to the site of transmigration. With the exception of disengaging the junctions, similar molecules and mechanisms promote transcellular migration as paracellular migration of leucocytes. This review will discuss the molecular interactions and signalling pathways that regulate transmigration, and the common themes that emerge from studying TEM of different leucocyte subsets under different inflammatory conditions. We will also raise some unanswered questions in need of future research.